2015
DOI: 10.3390/antibiotics4040435
|View full text |Cite
|
Sign up to set email alerts
|

Learning Processes and Trajectories for the Reduction of Antibiotic Use in Pig Farming: A Qualitative Approach

Abstract: Since 2011, French public policy has been encouraging a reduction in the use of antibiotics in animal farming. The aim of this article is to look at how some farms have already managed to lower their consumption of antibiotics, and to highlight the levers of change in farming health practices. Our research uses a qualitative study based on 21 semi-structured interviews with farmers and veterinarians in the French pig-farming sector. We use the notion of “trajectory of change” to examine, over time, the interse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
2
26
0
7
Order By: Relevance
“…These other factors are likely to be related to the country of origin, as the country of origin had a major effect in the multi-country model. They could relate, among others, to the structure of the pig sector, the regulation of antimicrobial usage or the influence of the socio-professional network of the farmer [15].…”
Section: Epidemiology and Infection 1011mentioning
confidence: 99%
See 1 more Smart Citation
“…These other factors are likely to be related to the country of origin, as the country of origin had a major effect in the multi-country model. They could relate, among others, to the structure of the pig sector, the regulation of antimicrobial usage or the influence of the socio-professional network of the farmer [15].…”
Section: Epidemiology and Infection 1011mentioning
confidence: 99%
“…Farmers who believed more strongly in their ability to reduce antimicrobial usage had higher intention to reduce it [13], and farmers who perceived higher risk of using antimicrobials had lower actual antimicrobial usage [14]. The social context and the professional network of the farmer, especially the relationship with the herd veterinarian or technical advisor, also strongly influences the farmer's practices in terms of antimicrobial treatments [15].…”
Section: Introductionmentioning
confidence: 99%
“…A close relationship between farmers and veterinarians was found to influence strategies for antibiotics use (Fortané et al, 2015). Jan et al (2012) indicated that social pressure, including consumer pressure, is another important factor influencing antibiotic use in farming.…”
Section: Studies On Farmersmentioning
confidence: 99%
“…Parmi les travaux mentionnés, certains ont abordé les questions à travers l' étude des trajectoires d' éleveurs ayant modifié leurs pratiques, ce qui a permis d'investiguer en parallèle les motivations des éleveurs et le déclic pour changer, la longueur et les modalités du processus, les évolutions techniques mises en oeuvre pour y parvenir, ainsi que l'accompagnement à l' extérieur de l' exploitation (Fortané et al, 2015 ;Samedi, 2015 ;Bonnet-Beaugrand et al, 2016). Les conditions techniques et sociologiques de la réussite de certaines actions de prévention ont été analysées parRoussel et Seegers (2012), Coutelet et al (2015) et par Fabreguettes (2017).…”
Section: Facteurs Influençant L'observance Par L'éleveur De Changemenunclassified